Automated psychophysical personality data acquisition system for human-robot interaction - Bhin, Hyeonuk; Choi, Jongsuk; Park, Sungkee; Lim, Yoonseob (2017 14TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2017)
This paper introduces an experimental method to collect various types of non-verbal cues for personality recognition that could be used for reliable human-robot interaction. The proposed system can record raw data of video, audio, and physiological signals through 9 different interaction scenarios and organize them for each scenario so that the data obtained by proposed system can be effectively used to find the possible correlation between non-verbal cues and human personality.